1991
DOI: 10.1159/000235439
|View full text |Cite
|
Sign up to set email alerts
|

Beta-2-Adrenoceptors of Polymorphonuclear Leukocytes in Children with Atopic Dermatitis

Abstract: [125I]-cyanopindolol (ICYP) was used in a binding assay to compare the number and affinity of β2-adrenoceptor binding sites on circulating polymorphonuclear leukocytes (PMN) of 21 children with atopic dermatitis (AD) and 23 age-matched controls. We found no correlation between the β2-adrenoceptor density and the age of the children in either collective. Furthermore, the number and affinity of β2-adrenoceptor binding sites on PMN was neither influenced by sex nor seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recent studies showed that neutrophils express both αARs and βARs including α 1A , α 2C , α 1D , β 1 , β 2 , and β 3 ARs but not α 2B ARs mRNA [52,[58][59][60][61][62][63]. The expression of αARs in neutrophils has been confirmed in multiple studies related to diverse physiological conditions [52,61].…”
Section: Catecholamines and Their Effects In Neutrophilsmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies showed that neutrophils express both αARs and βARs including α 1A , α 2C , α 1D , β 1 , β 2 , and β 3 ARs but not α 2B ARs mRNA [52,[58][59][60][61][62][63]. The expression of αARs in neutrophils has been confirmed in multiple studies related to diverse physiological conditions [52,61].…”
Section: Catecholamines and Their Effects In Neutrophilsmentioning
confidence: 87%
“…The potential role of β 2 ARs in other conditions such as psoriasis and atopic dermatitis appears to be controversial. Although there are some indications suggesting an irregularity in the function or expression of neutrophil β 2 ARs in psoriasis [77], posterior studies reported no change in the density and affinity of these receptor in neutrophils isolated of patients with psoriasis [78] or atopic dermatitis [59]. Moreover, neutrophil count in peripheral blood is also modulated by circadian oscillations by down-regulating CXCL-12 in the bone marrow, which can allow neutrophil release.…”
Section: Catecholamines and Their Effects In Neutrophilsmentioning
confidence: 99%
“…Ligand binding studies suggest that on average 1700–2200 β-AR are expressed on neutrophil membranes (Pohl et al, 1991 ; Schwab et al, 1993 ), while excluding the existence of α 2 -AR (Musgrave and Seifert, 1994 ). We have recently shown that human neutrophils express mRNA for all α- (with the only exception of α 2B -) and β-AR, in the following order: β 3 > β 2 > α 1A > α 1B ~ α 2A ~ β 1 = α 1D = α 2C and that exposure of cells to IL-8, a potent proinflammatory CXC-chemokine that promotes neutrophil chemotaxis and degranulation, increases mRNA levels of all AR, and that adrenaline, probably through the involvement of β-AR, profoundly affects neutrophil function (Scanzano et al, 2015 ).…”
Section: Adrenergic Modulation Of the Innate Immune Systemmentioning
confidence: 99%
“…Available evidence concern nearly only polymorphonuclear cells (PMN) and b-AR. Expression of b-AR on human PMN has been investigated only by means of ligand binding assays which indicated the existence on average of 1,700-2,200 binding sites per cell (Pohl et al 1991;Schwab et al 1993) or 39-61 fmol/mg of protein (Boreus et al 1986;Gurguis et al 1999b). In one study, the possible existence of a 2 -AR was excluded based on both ligand binding and functional experiments in either PMN and differentiated HL-60 cells, a promyelocytic cell line frequently used as a model for neutrophils (Musgrave and Seifert 1994).…”
Section: Granulocytesmentioning
confidence: 99%